The photographer's body: Populism, polarization, and the uses of victimhood in Venezuela - SAMET, ROBERT (American ethnologist, 2013)
Political antagonism between supporters and opponents of former president Hugo Chávez has been a defining feature of daily life in Caracas for more than a decade. Despite their different political orientations, the antagonistic poles of "chavismo" and "the opposition" share striking similarities, starting at the level of political practice. I argue that Venezuela's political polarization reflects the shared logic of populism. Through the story of Jorge Tortoza—a photojournalist killed during the failed 2002 coup d'état against President Chávez—I describe how the chavista–opposition divide is produced and policed through performances of victimhood, performances that are essential to populist mobilization in Venezuela.